BANCASSURANCE CONCEPT FROM THE PERSPECTIVE OF MONTENEGRIN MARKET - Miljana Novovic Buric; Vladimir Kascelan; Vladimir Kascelan (Economic Review)
Integrated services of financial institutions contribute to the quality and development of financial markets. The collaboration of banks and insurance companies through the bancassurance model, as the distribution channel of insurance products, results in reduction of business risk and costs of market research and achieves better profitability and other mutual benefits which have a positive effect on the performance of the insurance and financial markets. More specifically, the effective implementation of bancassurance provides benefits to banks, insurance companies, and to their customers. Although bancassurance has development perspective on the Montenegrin market, the paper will prove that adequate education and motivation of employees in the banking sector, as well as the adequate demand for this type of financial services, are necessary for its successful implementation. The purpose of this paper is to show the current trend of banks entering the insurance market in Montenegro and to point out the perspective and development problems of bancassurance in Montenegro.